Preclinical Assessment of Ursolic Acid Loaded into Nanostructured Lipid Carriers in Experimental Visceral Leishmaniasis - Jéssica Adriana Jesus; Ilza Maria Oliveira Sousa; Thays Nicolli Fragoso da Silva; Aurea Favero Ferreira; Márcia Dalastra Laurenti; Leila Antonangelo; Caroline Silvério Faria; Paulo Cardoso da Costa; Domingos de Carvalho Ferreira; Luiz Felipe Domingues Passero (MDPI AG, 2021)
Ursolic acid, a triterpene produced by plants, displayed leishmanicidal activity in vitro and in vivo; however, the low solubility of this triterpene limits its efficacy. To increase the activity of ursolic acid (UA), this triterpene was entrapped in nanostructured lipid carriers (UA-NLC), physical-chemical parameters were estimated, the toxicity was assayed in healthy golden hamsters, and the efficacy of UA-NLC was studied in experimental visceral leishmanisis. UA-NLC exhibited a spherical shape with a smooth surface with a size of 266 nm. UA-NLC displayed low polydispersity (PDI = 0.18) and good colloidal stability (−29.26 mV). Hamsters treated with UA-NLC did not present morphological changes in visceral organs, and the levels of AST, ALT, urea and creatinine were normal. Animals infected with Leishmania (Leishmania) infantum and treated with UA-NLC showed lower parasitism than the infected controls, animals treated with UA or Amphotericin B (AmB). The therapeutic activity of UA-NLC was associated with the increase in a protective immune response, and it was associated with a high degree of spleen and liver preservation, and the normalization of hepatic and renal functions. These data indicate that the use of lipid nanoparticles as UA carriers can be an interesting strategy for the treatment of leishmaniasis.